Gastrectomies for Gastroduodenal Ulcus - Viola Núñez, Humberto; Ant´unez da Graca, Carlos; Ram´´irez Pintos, Wilson; Huelmo Ozano, Roberto (Cirugía del Uruguay, 1980)
Case material consists of 78 gastrectomies performed in cases of gastroduodenal urcus, within the last 5 years, in Surgical Clinic N. 1 of Pasteur Hospital and in the Surgery Department of the Armed Forces Central Hospital of Montevideo.